Corruption discourse and modern state legitimation – a historical comparison of Britain and Germany - Booker, Martin (The University of Edinburgh, 2017)
This thesis examines the way in which corruption discourses are embedded in processes of state formation. It builds on the theoretical premise of social constructionism, namely that ‘corruption’ is not an entity that exists in reality but that it is an agreed-upon classification of certain types of behaviours. These processes of social and political construction are foundational for corruption discourse, conceptualised as a political practice through which the legitimacy of power and authority, of either persons, behaviours or institutions, can be challenged. As a socially and politically constructed entity, corruption discourse is shaped by political processes and in turn also shapes political processes. The comparison of corruption discourses in Britain in the 19th century and in Germany in the late 19th to mid-20th centuries endeavours to demonstrate the different ways in which they were shaped, as well as in turn shaped, contextual state formation processes. The two countries represent two different pathways through which high levels of corruption control were achieved, one democratic, the other authoritarian. While anti-corruption measures in Britain were introduced alongside democratisation processes in the 19th century, various German states implemented measures top-down in their 18th century efforts to modernise state administration. This study looks at the times when corruption discourses became a matter of public interest, and traces their role vis-a-vis subsequent institutional developments. In Britain this starting point is located in the early 19th century, in Germany in the Kaiserreich of the 1870s. Three case studies each exemplify and illustrate the different sequences in which corruption discourse unfolded. In Britain, these are the 1809 Duke of York case, exemplifying a ‘discovery phase’, in which corruption discourse first showed signs of becoming weaponised for political discourse; the 1830 to 32 Electoral Reform discourse exemplifying a ‘contestation phase’ in which corruption allegations were strategically used to undermine the legitimacy of Parliament and the system through which it was elected; and the 1889 Corrupt Practices Act discourse, exemplifying a ‘consolidation phase’ in which anticorruption measures became normalised rather than being subject to contest. In Germany, the 1896/97 Tausch Affair represents a different kind of discovery phase, one that is restrained and corrupted by authoritarian intervention; the Erzberger-Helfferich case of 1919 represents a different kind of contestation phase, one that is characterised by the hyper-mobilisation of corruption discourse that contributed to the eventual failure of the Weimar Republic; and the Spiegel Affair of 1962, in the context of the Spiegel’s role in post-war Germany more broadly, represents a successful consolidation phase in the Bundesrepublik, in which authoritarian intervention failed to corrupt corruption discourse. The cases thus highlight different ways in which corruption discourse was shaped by, and in turn shaped, state formation processes. They showcase a range of different institutional and political framework conditions as well as a variety of institutional outcomes, of reform, consolidation and destruction. The thesis argues that corruption discourse was thus a central driver of state formation processes, and that concepts of corruption were integral to the idea of the modern state.
Keywords: corruption; discourse; modern states; legitimation; Great Britain; Germany